Conceptual modeling : 34th International Conference, ER 2015, Stockholm, Sweden, October 19-22, 2015, proceedings /: 34th International Conference, ER 2015, Stockholm, Sweden, October 19-22, 2015, proceedings. (2015) - Unknown
No abstract available